The Effect of Work Environment, Reward, and Organization Culture on Employee Performance Through Job Satisfaction as Intervening Variables - Fatma, Kurnia; Latif , Muhamad; Wijaya, Mochamad Hadi; Nilasari , B. Medina; Nisfiannoor , M. (Archives of Business Research, 2023)
The purpose of this empirical study is to analyze the influence of the Work Environment, Rewards, Organizational Culture on Employee Performance which is mediated by Job Satisfaction. The data used in this research is primary data taken by distributing questionnaires using a purposive sampling method involving 190 frontliner employees of state-owned banks in South Jakarta, Indonesia. The analytical tool in this study is Structural Equation Modeling (SEM) using AMOS version 24. The results of this study are that there is a positive and significant effect of work environment and rewards on job satisfaction, but organizational culture has no effect on job satisfaction, there is a positive and significant effect work environment and job satisfaction on employee performance, but rewards and organizational culture have no effect on employee performance. there is a positive and significant effect of work environment and rewards on employee performance through the mediation of job satisfaction. However, organizational culture has no effect on employee performance through the mediation of job satisfaction. From the results of this study, it is recommended that state- owned banks should provide a clean and comfortable workplace for frontliner employees, and encourage supervisors to appreciate the work of frontliner employees by giving praise or recognition.